2014
DOI: 10.1371/journal.pone.0106510
|View full text |Cite
|
Sign up to set email alerts
|

Use of High Throughput Sequencing and Light Microscopy Show Contrasting Results in a Study of Phytoplankton Occurrence in a Freshwater Environment

Abstract: Assessing phytoplankton diversity is of primary importance for both basic and applied ecological studies. Following the advances in molecular methods, phytoplankton studies are switching from using classical microscopy to high throughput sequencing approaches. However, methodological comparisons of these approaches have rarely been reported. In this study, we compared the two methods, using a unique dataset of multiple water samples taken from a natural freshwater environment. Environmental DNA was extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
10
50
0
Order By: Relevance
“…Ten studies focused on a broad range of eukaryotic biodiversity (e.g. Pawlowski et al 2011;Baldwin et al 2013), whereas only three of the studies targeted both prokaryotic and eukaryotic organisms (Xiao et al 2014;Young et al 2014;Kowallik et al 2015). Just over 10% of the studies investigated fungi (e.g.…”
Section: Organisms Studiedmentioning
confidence: 99%
“…Ten studies focused on a broad range of eukaryotic biodiversity (e.g. Pawlowski et al 2011;Baldwin et al 2013), whereas only three of the studies targeted both prokaryotic and eukaryotic organisms (Xiao et al 2014;Young et al 2014;Kowallik et al 2015). Just over 10% of the studies investigated fungi (e.g.…”
Section: Organisms Studiedmentioning
confidence: 99%
“…In recent years, novel molecular tools have replaced classical DNA Sanger sequencing in aquatic microbiology; quantitative PCR, high throughput sequencing, metatranscriptome and proteome analyses are increasingly being used to characterise taxonomic and functional diversity of (marine) microorganisms including phytoplankton (reviewed by Johnson & Martiny, 2015). However, quantification of the entire phytoplankton species composition and biomass is still difficult with the molecular protocols currently available (Johnson & Martiny, 2015;Xiao et al, 2014), and the application of the molecular tools by monitoring agencies has been limited (e.g. Wollschläger et al, 2014;Wood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to TOM, HTS can detect a wide variety of plankton, including nanoplankton and rare taxa. Other studies also found similar results in freshwater ecosystems [32,34,50,52]. Xiao et al (2014) [32] found that the species compositions detected by TOM and 454 HTS did not always match at the taxa level after analyzing 300 weekly water samples over 20 years in Lake Gjersjøen, Norway, a drinking water source.…”
Section: Discussionmentioning
confidence: 58%
“…Other studies also found similar results in freshwater ecosystems [32,34,50,52]. Xiao et al (2014) [32] found that the species compositions detected by TOM and 454 HTS did not always match at the taxa level after analyzing 300 weekly water samples over 20 years in Lake Gjersjøen, Norway, a drinking water source. Studies in Lake Tegel, Germany, showed that because the 480 used diatom sequences of the 18S region were generated from world-wide occurrences, only a small number of individuals precisely matched on the species level [52].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation